2014
DOI: 10.1590/1678-775720130570
|View full text |Cite
|
Sign up to set email alerts
|

The combined use of Er,Cr:YSGG laser and fluoride to prevent root dentin demineralization

Abstract: The use of erbium lasers to prevent caries in enamel has shown positive results. However, it is not known if Er,Cr:YSGG laser can also be used to increase acid resistance of root dentine, which is another dental tissue susceptible to the action of cariogenic bacteria.ObjectiveTo analyze the effects of the Er,Cr:YSGG laser (λ=2.78 μm, 20 Hz) irradiation associated with 2% neutral sodium fluoride (NaF) to prevent root dentin demineralization.Material and MethodsOne hundred human root dentin samples were divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Geraldo-Martin et al 18 (2013) showed that irradiation of Er,Cr:YSGG laser with 4.64 J/cm 2 energy density along with water coolant further opened the dentinal tubules; they concluded that use of water coolant during laser irradiation for prevention of caries in dentin is not much effective since it results in further opening of dentinal tubules, which probably leads to faster progression of caries in dentin. Later in 2014, Geraldo-Martin et al 2 showed that Er,Cr:YSGG laser irradiated with 8.92 J/cm 2 energy density without water coolant created brown spots on root dentin, which were microscopically shown to be burned dentin due to overheating. They demonstrated that high power Er,Cr:YSGG laser without water coolant caused significant thermal damage in dentin and made it more susceptible to acidic challenge.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Geraldo-Martin et al 18 (2013) showed that irradiation of Er,Cr:YSGG laser with 4.64 J/cm 2 energy density along with water coolant further opened the dentinal tubules; they concluded that use of water coolant during laser irradiation for prevention of caries in dentin is not much effective since it results in further opening of dentinal tubules, which probably leads to faster progression of caries in dentin. Later in 2014, Geraldo-Martin et al 2 showed that Er,Cr:YSGG laser irradiated with 8.92 J/cm 2 energy density without water coolant created brown spots on root dentin, which were microscopically shown to be burned dentin due to overheating. They demonstrated that high power Er,Cr:YSGG laser without water coolant caused significant thermal damage in dentin and made it more susceptible to acidic challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, laser irradiation must be necessarily accompanied by water-cooling to prevent damage to pulp and dentin; however, the amount of water must be minimal in order not to compromise the anti-caries effects of laser irradiation. 2 Therefore, we also used a combination of water (60%) and air (80%) coolant in our study. The chosen laser powers in our study (0.25, 0.5, 0.75 and 1W) were based on a previous study by de Freitas et al, 16 since these powers conferred optimal resistance to enamel in their study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier studies using other fluoride gels have been shown to significantly reduce dentinal hypersensitivity and improve dentinal tubule occlusion. [ 13 27 ]…”
Section: Discussionmentioning
confidence: 99%